I am Michael [videorecording (DVD)] - Kelly, Justin (Director); Franco, James, 1978-; Roberts, Emma, 1991-; Hannah, Daryl; Quinto, Zachary (Passion River, 2017)
Based on the true-life story of Michael Glatze, a gay activist who becomes an anti-gay Christian pastor. Michael is a high profile gay youth activist who created a national controversy when he claimed to no longer be gay and became a straight Christian pastor. The film follows Michael from his life in San Francisco with his boyfriend Bennett--where he pursues political activism, a journalist career at XY Magazine, social awareness, and sexual exploration--to his days of personal self-discovery. After a traumatic scare, Michael is plagued by doubt and paranoia, and begins a religious reawakening. Michael renounces his gay lifestyle, rejects his friends, and endeavors to find his "true self." He explores Buddhism and Mormonism, yet ultimately lands at a Christian Bible school in rural Wyoming where he meets his girlfriend Rebekah, and becomes the pastor of his own church.